In-vitro anti-inflammatory activity and anti-arthritic activity of ethyl acetate extracts of Skimmia anquetilia leaves: anti-inflammatory activity and anti-arthritic activity of Skimmia anquetilia leaves - Verma, Poonam; Singh, Baljinder; Kaur, Amarjit; Kumar, Vijender (Journal of Medicinal Herbs and Ethnomedicine, 2020)
Current investigations were carried out for the validation of in-vitro anti-inflammatory and anti-arthritic property of leaves of Skimmia anquetilia using red blood cells membrane stabilization and protein denaturation methods respectively. Defatted ethylacetate extracts at different concentration levels (50, 100, 200 and 400 mg/ml) were used in these studies. Dose dependent inhibition of protein denaturation was found 92.41% at 400 mg/ml of extracts and 96.21 % at 100 mg/ml of acetyl salicylic acid as standard in antiarthritic study. Similarly, in membrane stabilization methods, maximum effect found 90.70 % at 400 mg/ml of extracts and 94.88 % at 100 mg/ml of diclofenac sodium as standard for anti-inflammatory evaluation. The results concluded that, ethyl acetate extract of S. anquetilia leaves has shown significant (*aP<0.05) anti-inflammatory and anti-arthritic effects.